Laparoscopic Dismembered Pyeloplasty for Ureteropelvic Junction Obstruction: Our Preliminary Experience (Bangladesh Journal of Urology, 2020)
Objective: To evaluate prospectively the results obtained in 16 patients undergoing laparoscopic pyeloplasty through transperitoneal access.Materials and Methods: The study was conducted in the department of urology, BSMMU, Dhaka between the periods of March 2013 and June 2014, sixteen patients between 15 and 48 years old, were treated for ureteropelvic junction obstruction (UPJO) via a transperitoneal laparoscopy. All patients had clinical symptoms of urinary obstruction and hydronephrosis were confirmed by imaging methods. Anderson-Hynes dismembered pyeloplasty was performed in all patients. Patients were clinically and imaging evaluated in the postoperative period at 6 and 12 weeks.Results: Most of the patients were male (68.75%) and female were 31.25%. The mean operative time was 127.37 (±15.67) minutes ranged from 95 to 240 minutes. Pain score in first postoperative day and third postoperative day following pyeloplasty were 20.87 (±6.83) and 4.75 (±3.34) respectively. The mean hospital stay was 4.25 (±1.34) days. Anomalous vessels were identified in 4 patients, intrinsic stenosis in 12 patients. Postoperative urine leakage and UTI were seen 18.75%, 12.50% subject respectively. Split renal function and GFR were significantly improved (p